FAKTOR-FAKTOR YANG MEMPENGARUHI ANGKA KUMAN PADA PERALATAN MAKAN DI LAPAS WANITA KLAS IIA SEMARANG - Rona Arundina Rahmadiani; Sulistyani Sulistyani; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
Prison is a place coaching and protege correctional prisoners in Indonesia. They have the same rights as other members of society to achieve the level of health, one of which is food. Therefore, food hygiene are concerned. Tableware plays an important role in the occurrence of food poisoning. According to data from the Directorate General of Communicable Disease Control, 30% of cases of poisoning caused by food or catering cutlery services that are not clean. Kepmenkes no.1908 2003 mentions the equipment in direct contact with food must not contain germs> 100 colonies / cm2. This study aims to determine the factors that influence the number of bacteria on the cutlery in the female prison Semarang class IIA. Research conducted on 51 respondents with cross sectional approach. The research result shows the characteristics of respondents aged 26-35 is the most respondents with elementary and junior high education level and length of stay 1-5 years. Conclusion of the study is a factor that affects the amount of germs among other equipment washing technique (p = 0.002) and storage of cutlery (p = 0.000). Suggestion research is necessary to hold training equipment washing and improve tableware storage facilities.